Challenging the Frontiers of Poverty Reduction (CFPR) - targeting the ultra poor - targeting social constraints: Volume 2, 2000 - BRAC (© BRAC, 2016)
1. Executive Summary of Appraisal mission's Report 2. Summary and Detailed Budget 3. Notes to CFPR Budget 4. Staff Requirement for CFPR 5. Enterprise Economics 6. Existing NGO Programmes for Ultra Poor 7. Bangladesh, Poverty and BRAC 8. The Impact of BRAC: Various Research Findings 9. Jamalpur Flood Rehabilitation Report (ECHO) 10. Focus Note on IGVGD Programme.